Bathsheba's Choice : Female Agency in Thomas Hardy's Far from the Madding Crowd - Kempas, Viivi (My University, 2025)
Thomas Hardy’s Far from the Madding Crowd explores themes of female agency and independence through its protagonist Bathsheba Everdene, who inherits her uncle’s wealth as a young, unmarried woman in the nineteenth century. This elevates her status in society and affords her the privilege to make her own decisions in matters of finances and personal freedom. This thesis examines the characterisations of Bathsheba and the three men who wish to marry her, with a focus on their relationships with her and the ways in which they interact with and influence her. An analysis of Hardy’s writing in a historical context provides insight into Victorian gender norms, societal expectations and how these subjects factor into and shape the characters’ choices and relationships. The examination of the novel highlights the central element of female agency, and the choices Bathsheba makes reflect a broader commentary on it.
Keywords: Far from the Madding Crowd, Thomas Hardy, Bathsheba, agency, female protagonist, Victorian era literature